Induksi of Porphyromonas gingivalis Meningkatkan Proporsi Endotelin-1 pada Aorta Mencit yang Diinduksi Diet Aterogenik - Elyani, Helmin Elyani; Hernowati, Tinny Endang; Sumarno, Sumarno (Jurnal Kedokteran Brawijaya, 2009)
One of the risk factor of atherosclerosis is associated with activation of the inflammatory process in infection,as evidence by systemic elevations of molecules such as MCP-1,PAI-1 and ET-1. Recent evidence suggeststhat infectious agents, including those that cause periodontal disease, may also important role inatherosclerosis. The aim of this study was to determine if recurrent intravenous injections with P. gingivalis for14 weeks promotes endothelial smooth muscle ET-1 proportion in aortic mice. Twenty four weeks old mice(n=6 per group for each time point) were divided in two groups, there were normal diet and atherogenic diet,each of them were inoculated intravenously with live P. gingivalis (10 cell/50Âµl PBS) injections or vehicle (50Âµl PBS) once per week for 14 weeks. The Immunohistochemistry for aortic ET-1 proportion were performed.The result of RAK with 3 interaction and Tukey test using SPSS 14 for windows showed that at 14 weeks, theET-1 proportion in aortic endothelial cell was higher than in aortic smooth muscle cell.